Effects of strain rate and high temperature environment on the mechanical performance of carbon fiber reinforced thermoplastic composites fabricated by hot press molding. (July 2020) - Zhang, Yiben; Sun, Lingyu; Li, Lijun; Wei, Junlei
Abstract: The mechanical performance of continuous large tow carbon fiber reinforced polyamide 6 laminates fabricated by hot press molding was studied using quasi-static and dynamic tests. The effects of layup, strain rate and high temperature were discussed. The results show that the thermoplastic composites possess strain rate strengthening effects and high temperature weakening dependence. Different layup laminates exhibit different sensitivities. The elastic modulus difference of unidirection/cross-ply laminates decreases but that of unidirection/quasi-isotropic or unidirection/angle-ply laminates increases with the increasing strain rate. However, the failure strength difference changes insignificantly as the strain rate increases. The modulus or strength difference between unidirectional laminate and the other laminates decreases with the increasing temperature. The weakening effect of high temperature is stronger than the strengthening effect of strain rate for tensile mechanical properties. Furthermore, the failure behavior and mechanism were analyzed. These experimental data and research results could provide some insight for high-performance thermoplastic composites.